HAK ATAS LINGKUNGAN HIDUP DILIHAT DALAM PERSPEKTIF HUKUM POSITIF DI INDONESIA - Permadhi, Putu Lantika Oka (Jurnal Hukum Saraswati (JHS), 2019)
Violations of human rights (HAM) in the environmental field have occurred in almost all levels of community life. The violation should be interpreted as a threat to Indonesian human civilization. In turn it accumulates and leads to violations of economic rights, violations of social and cultural rights, civil and political rights. The phenomenon of the right to a good, healthy and balanced environment as a human right, related to the reality of environmental management in Indonesia has not yet been realized. Related to the issue of environmental damage, the right to the environment in the perspective of human rights is interesting to be examined and studied, in order to describe the conception of human rights and the right to the environment, the regulation of the right to the environment in Indonesia's positive legal provisions, the right to the environment good and healthy is a human right, and its implementation in environmental management policies.